2014
DOI: 10.3109/14647273.2014.965759
|View full text |Cite
|
Sign up to set email alerts
|

Seminal insulin-like growth factor-I may be involved in the pathophysiology of infertility among patients with clinical varicocele

Abstract: Varicocele, the most common cause of male infertility, is defined as abnormal dilation of the pampiniform plexus. Although different mechanisms have been proposed to explain the pathophysiology of infertility caused by varicocele, it is still open to debate. Previous studies have demonstrated the effect of insulin-like growth factor-I (IGF-I) on semen quality in animals and humans, but there are no studies on the probable role of seminal IGF-I in the pathophysiology of infertility among patients with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…Early human studies have shown the presence of IGF-I, IGF-II, IGFBP-2, IGFBP-3 fragments, IGFBP-4, IGFBP-5, IGFBP-protease activities and PSA in SP [14,18,19,27,[37][38][39], while recent studies have reported that SP IGF-I levels do not differ between men with normal and abnormal semen parameters [15,20]. Evidence that vasectomized patients had lower SP IGF-I levels than intact patients suggests that SP IGF-I is mainly of testicular origin [39], whereas in patients with varicocele (a common cause of male infertility), higher SP IGF-I levels than healthy fertile men have been observed implying a role of localized IGF-I in the pathogenesis of male infertility [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early human studies have shown the presence of IGF-I, IGF-II, IGFBP-2, IGFBP-3 fragments, IGFBP-4, IGFBP-5, IGFBP-protease activities and PSA in SP [14,18,19,27,[37][38][39], while recent studies have reported that SP IGF-I levels do not differ between men with normal and abnormal semen parameters [15,20]. Evidence that vasectomized patients had lower SP IGF-I levels than intact patients suggests that SP IGF-I is mainly of testicular origin [39], whereas in patients with varicocele (a common cause of male infertility), higher SP IGF-I levels than healthy fertile men have been observed implying a role of localized IGF-I in the pathogenesis of male infertility [17].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the role of IGFs and IGFBPs in the male reproductive system has been less well studied. Although the presence of IGFs and IGFBPs have been demonstrated in SP [14][15][16][17][18][19][20], it remains unclear what these levels are in infertile men with low sperm motility versus those with low sperm counts, and if they exert a speci c functional role in affecting sperm characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, IGF‐1 receptor (IGF‐1R) was shown to be absent from the seminal plasma of patients with a history of failed fertilisation, although IGF‐1R was present both in fertile and infertile men (Sánchez‐Luengo, Fernández, & Romeu, ). IGF‐1 levels in seminal plasma from patients with varicocele‐a common cause of male infertility were significantly different compared with those following varicocelectomy and those of the control group, although IGF‐1 was not correlated with semen quality (Naderi, Mohseni Rad, Tabassomi, & Latif, ). With regard to animal models, IGF‐binding protein‐1 (IGFBP‐1) overexpression in transgenic mice showed an alteration of spermatogenesis resulting in lower production and quality of sperm (Froment et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Early human studies have shown the presence of IGF-I, IGF-II, IGFBP-2, IGFBP-3 fragments, IGFBP-4, IGFBP-5, IGFBP-protease activities and PSA in SP [14,18,19,27,[37][38][39], while recent studies have reported that SP IGF-I levels do not differ between men with normal and abnormal semen parameters [15,20]. Evidence that vasectomized patients had lower SP IGF-I levels than intact patients suggests that SP IGF-I is mainly of testicular origin [39], whereas in patients with varicocele (a common cause of male infertility), higher SP IGF-I levels than healthy fertile men have been observed implying a role of localized IGF-I in the pathogenesis of male infertility [17].…”
Section: Discussionmentioning
confidence: 99%